PENGARUH WAKTU MASERASI TERHADAP AKTIVITAS ANTIOKSIDAN EKSTRAK RIMPANG TEMULAWAK (Curcuma xanthorriza Roxb.) - Amelinda, Ega; Widarta, I Wayan Rai; Darmayanti, Luh Putu Trisna (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2018)
This research aimed to find effect of maceration time on antioxidant activity of java turmeric rhizome extract and to get the right maceration time with highest antioxidant activity of java turmeric rhizome extract. This study used The Completely Randomized Design with the treatment of maceration time of 6 levels: 18 hours, 24 hours, 30 hours, 36 hours, 42 hours and 48 hours. The experiment was repeated in three replication, so that 18 experimental units were obtained. Data were analyzed by Analysis of Variance (ANOVA) and then continued with Duncan Multiple Range Test (DMRT). The result showed that the treatment of maceration time had very significant effect on extraction yield, total curcumin, total phenol and antioxidant activity of java turmeric rhizome extract. The best treatment was 24 hours with extraction yield was 18.88%, total phenol 205.86 mg GAE/g, total curcumin 21.22 mg/g extract, antioxidant activity 84.45% and IC 50 36.96 mg/L.